Developing Local-Content Agricultural Reading Materials for Freshmen - Ketut Armawan; Kadek Andre Karisma Dewantara; Luh Sri Damayanti; Salsabila Gita Nurani; Asti Siti Nurazizah (Didascein : Journal of English Education, 2026)
This study developed and evaluated agricultural local-content-based instructional reading materials alongside a Group Reading Assessment (GRA) instrument for English as a Foreign Language (EFL) freshmen at STIPER Belitang, an agricultural college in South Sumatra, Indonesia. Employing Akker's (1999) developmental research framework and Tessmer's (1993) formative evaluation model, this investigation addressed a critical yet underexplored gap—the systematic absence of contextualized English reading resources integrating authentic local agricultural content for Indonesian university freshmen. The materials were validated by expert reviewers and tested through one-to-one, small group, and field trial phases. Results confirmed high validity (M = 3.10), high practicality (M = 3.12 and 3.08, respectively), and significant criterion-related validity (r = 0.711 for reading materials; r = 0.812 for the GRA). The field test further revealed that 71.4% of students surpassed the minimum mastery criterion, affirming the products' potential effectiveness. This study contributes a replicable, context-sensitive framework for ESP material development that bridges language learning with students' immediate agricultural environment, thereby enhancing both learner engagement and reading comprehension outcomes.